A Corporate Governance Model : Building Responsible Boards and Sustainable Businesses - World Bank (Washington, DC, 2012)
The foundation of good corporate governance is the intellectual honesty of directors and senior management. This intellectual honesty is expressed by acting in the best interests of the incapacitated company. The company, on formation, is a person, but it is absolutely incapacitated until its directors are appointed and the board in turn delegates to management the implementation of its collective decisions. It is the quality of governance that is important and not the quantity. Mindless compliance with a set of rules is not good governance. Good governance connotes acting with responsibility, accountability, fairness and transparency. Transparency has a withering effect on misconduct and is absolutely critical in communicating to stakeholders any decisions of the board. In this context, transparency demands that the communications consist of substance over form and contain positive and negative aspects, if any. The board of directors is the most important element in corporate structures. Issues such as the composition of the board of directors, the issues that the board focuses on, processes they follow for decision making and how they learn to continuously improve the governance of the corporation critically influence the quality of decisions and the management quality. The main responsibilities of the board are to provide an effective oversight for the management and guidance to the corporation with value creating strategies. The quality of their decisions is critically dependent on the quality of the information they have. Establishing a culture that sets the right tone at the top is critical for establishing the 'trust' for the corporation.